Enrichment of fresh pasta type talharim with seafood flour (Anomalocardia brasiliana) (Research, Society and Development, 2020)
Noodles are high in carbohydrates and low in protein quality and quantity. However, it is one of the most consumed foods by the population. In view of this situation, this work aims to prepare to evaluate fresh noodle-type pasta enriched with different concentrations of shelfish. Five types of pasta, a traditional pasta sample, three samples with different concentrations of shellfish (5%, 10% and 15%) and another sample with the association between seafood and flaxseed (5% + 5%) were prepared. Samples were evaluated and analyzed for moisture content, lipids, proteins, fiber, ashes, carbohydrates and total caloric value of the product. A completely randomized design with three replicates of each concentration was adopted, determining the mean and standard deviation of the values obtained for each sample. The formulations with higher amount of shellfish presented higher protein content, ash and lower carbohydrate content. The addition of golden flaxseed in the pasta noodles with shellfish provided an increase in the value of crude fiber and ethereal extract. The enrichment of the pasta with different concentrations of shellfish increased the protein value of the new product, as well as presenting a great and important alternative to add a more relevant nutritional aspect to the food.